A review of anhidrosis in horses. (28th August 2014) - MacKay, R. J.; Mallicote, M.; Hernandez, J. A.; Craft, W. F.; Conway, J. A.
Summary Horses with anhidrosis are defined by signs of impaired thermoregulation caused by sweating that is inadequate for the ambient conditions. Anhidrosis has been recognised since the early twentieth century; affected horses have been variably described as nonsweaters, drycoats, blowers or puffers. The condition affects horses of all age groups, breeds, coat colours, genders and activities and is common among horses in hot, humid environments. Despite the enormous financial and emotional costs of anhidrosis, the causes and pathogenesis of the condition are largely unknown and no consistently effective treatment has been found.